2012
DOI: 10.1021/es203642e
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of CL-20-Induced Reversible Neurotoxicity Reveals GABAAReceptors as Potential Targets in the EarthwormEisenia fetida

Abstract: The earthworm Eisenia fetida is one of the most used species in standardized soil ecotoxicity tests. Endpoints such as survival, growth and reproduction are eco-toxicologically relevant but provide little mechanistic insight into toxicity pathways, especially at the molecular level. Here we applied a toxicogenomic approach to investigate the mode of action underlying the reversible neurotoxicity of hexanitrohexaazaisowurtzitane (CL-20), a cyclic nitroamine explosives compound. We developed an E. fetida-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…One hundred ng of total RNA was first reverse-transcribed into cDNA, followed by cDNA labeling using Low Input Quick Amp Labeling Kits (Agilent, Palo Alto, CA) in the presence of cyanine 3-CTP dye. The labeled cDNA was hybridized to the C. elegans -specific 44 K-olig array (one sample/array) at 65 °C for 17 h using Agilent’s Gene Expression Hybridization Kits [ 39 ]. A total of 48 samples (3 chemicals × 4 treatments per chemical × 4 replicates per treatment) were randomly assigned and hybridized to six 8 × 60 K-array slides containing 44 K oligonucleotide probes per array.…”
Section: Methodsmentioning
confidence: 99%
“…One hundred ng of total RNA was first reverse-transcribed into cDNA, followed by cDNA labeling using Low Input Quick Amp Labeling Kits (Agilent, Palo Alto, CA) in the presence of cyanine 3-CTP dye. The labeled cDNA was hybridized to the C. elegans -specific 44 K-olig array (one sample/array) at 65 °C for 17 h using Agilent’s Gene Expression Hybridization Kits [ 39 ]. A total of 48 samples (3 chemicals × 4 treatments per chemical × 4 replicates per treatment) were randomly assigned and hybridized to six 8 × 60 K-array slides containing 44 K oligonucleotide probes per array.…”
Section: Methodsmentioning
confidence: 99%
“…There may be a neuronal membrane depolarization in a reversible manner and an increased level of free calcium which could be either or due to its release from the organelle or inhibition on its reuptake. 42 The oxidant/antioxidant status of the worms did show significant changes beyond the concentration of 7.0 mg/kg bw of ACR leading toan imbalance is exacerbating loss of ionic imbalance. It is assumed that the oxidative stress and membrane potential have a role in the sensory modulation of locomotion movements in the annelids.…”
Section: Discussionmentioning
confidence: 92%
“…Among them, CL-20 (1) is the most wellknown representative and extensive studies have confirmed its xenobiotic nature (Figure 1). Toxicology studies investigating the effects of high doses of CL-20 on animal organisms have revealed that its negative impact, mediated through various biotransformation pathways, is mostly reversible [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interestingly, current genetic research methods demonstrate the reversibility of the neurotoxic effects of compound 1 on Eisenia fetida [11].…”
Section: Introductionmentioning
confidence: 99%